PENGARUH DIGITAL MARKETING DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA YAMUNA PASTRY - Ni Made Maria Magdalena; Saortua Marbun (Universitas Triatma Mulya, 2022)
This research is motivated by the phenomenon of purchasing decisions at Yamuma Pastry. This study aims to analyze and prove the influence of digital marketing and product attributes on purchasing decisions. This study uses quantitative methods. The sampling technique used is purposive sampling technique. The number of respondents used is 75 consumers. Multiple linear regression analysis using SPSS software version 24. Regression equation obtained: Y = 13.199 + 0.218X1 + 0.452X2. The results of this study indicate that: First, digital marketing has a positive effect on purchasing decisions at Yamuma Pastry. Second, product attributes have a positive effect on purchasing decisions at Yamuma Pastry.